Personal Traits of Teachers and Their Relationship to Their Job Satisfaction in The Sultanate of Oman - Al-Thohli, Hilal Shamis Hamad; Al-Abri, Nasra Saleh Abdullah (Journal of Educational and Psychological Sciences, 2023)
This study aimed to identify the personal characteristics of teachers and their relationship to their job satisfaction in the Sultanate of Oman, and the effect of the variables (gender, years of experience). To achieve its aims, the researchers used the descriptive correlative method by designing a questionnaire applied randomly to (505) male and female teachers. The results of the study revealed that the study sample members’ estimates of the personal traits of teachers and job satisfaction in the Sultanate of Oman were a large degree for each of them and there were no statistically significant differences at the significance level (α = 0.05) for teachers’ personal traits due to the gender variable in all domains, with the exception of the fifth domain “conscience vigilance”, there are statistically significant differences in favor of females and there were no statistically significant differences at the significance level α = 0.05 for teachers’ personal traits due to the variable years of experience in all domains. Additionally, the results showed that there were no statistically significant differences at the significance level α = 0.05 between the average teachers’ estimates of teachers’ job satisfaction due to the gender variable in all domains, except for the fourth domain “salaries and incentives” with the presence of statistically significant differences in favor of females, and there were no statistically significant differences at the significance level α = 0.05 due to the variable years of experience in all domains, Except for the third domain, "Human Relations", there were statistically significant differences in favor of 16 years and over, and the results showed a weak positive correlation between the personal traits of teachers in the Sultanate of Oman and their job satisfaction. In the light of the results, The study recommends that, holding courses for teachers in order to strengthen their self-concept, and working to improve and raise incentives and promotions for teachers, in addition to design a proposal for a study to reveal the obstacles facing teachers’ job satisfaction.